2022
DOI: 10.3389/fimmu.2022.948658
|View full text |Cite
|
Sign up to set email alerts
|

Esaxerenone inhibits the macrophage-to-myofibroblast transition through mineralocorticoid receptor/TGF-β1 pathway in mice induced with aldosterone

Abstract: Renal fibrosis is the inevitable pathway of the progression of chronic kidney disease to end-stage renal disease, which manifests as progressive glomerulosclerosis and renal interstitial fibrosis. In a previous study, we observed severe interstitial fibrosis in the contralateral kidneys of 6-month unilateral ureteral obstruction (UUO) rats, which was accompanied by increased macrophage infiltration and phenotypic transformation; after eplerenone administration, these effects were reduced. Therefore, we hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This finding was also validated in RAW264.7 cells cultured in vitro and suggested that UUO-induced macrophage infiltration generated a favorable microenvironment for lymphangiogenesis and was involved in lymphangiogenesis through the secretion of VEGFC. These macrophages, which may originate from the bone marrow or from in situ proliferation of kidney macrophages, may be activated by MR, the inflammatory cytokines IL-1β and TNF-α or hypoxia-inducible factor 21 , 23 26 . In addition, renal tubular epithelial cells can also be sources of VEGFC in response to renal injury 24 , 27 , which remains to be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also validated in RAW264.7 cells cultured in vitro and suggested that UUO-induced macrophage infiltration generated a favorable microenvironment for lymphangiogenesis and was involved in lymphangiogenesis through the secretion of VEGFC. These macrophages, which may originate from the bone marrow or from in situ proliferation of kidney macrophages, may be activated by MR, the inflammatory cytokines IL-1β and TNF-α or hypoxia-inducible factor 21 , 23 26 . In addition, renal tubular epithelial cells can also be sources of VEGFC in response to renal injury 24 , 27 , which remains to be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we observed that macrophages in the kidney or heart were involved in fibrosis via macrophage-to-myofibroblast transition (MMT) in UUO rats and aldosterone-infused mice, which was associated with inflammatory injury induced by aldosterone-stimulated MR activation [45][46][47]. MR activation leads to macrophage infiltration and MMT, which participates in fibrosis by secreting the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty mice were randomly assigned to the CON group, ALD group (aldosterone group), and ESA group (aldosterone + esaxerenone group) (n = 10 each). Aldosterone is infused with a mini-osmotic pump (0.75 mg/h, ALZET model 2006, DURECT Corporation, Cupertino, CA, USA) as described in a previous paper [47]. Esaxerenone (kindly provided by Daiichi Sankyo Co., Ltd., Tokyo, Japan) was administered to the ESA group via diet at a dose of 1 mg/kg diet for 12 weeks, and the other groups were fed regular chow.…”
Section: Animals and Experimental Modelsmentioning
confidence: 99%
See 2 more Smart Citations